The Role of Digital Literacy, Public Policy, and Community Participation in Increasing Environmental Awareness in Indonesia - Istifa, Much Al Khaqqoh; Ali, Husain (The Eastasouth Journal of Social Science and Humanities, 2025)
This study aims to examine the role of digital literacy, public policy, and public participation in increasing environmental awareness in Indonesia. Through multiple linear regression analysis, this study evaluates the influence of these three variables on environmental awareness, involving 300 respondents from various regions in Indonesia. The results show that digital literacy, public policy, and public participation have a significant positive effect on environmental awareness. Digital literacy allows people to access information about environmental issues more quickly and widely, good public policies provide clear directions regarding environmentally friendly behavior, and public participation encourages active involvement in preserving the environment. The synergy between these three factors is essential in creating greater awareness of the importance of environmental conservation in Indonesia. This study provides theoretical and practical contributions in identifying effective strategies to increase environmental awareness through digital literacy, appropriate policies, and public participation.